Floating-fixed-bed-gasification: From Vision to Reality. (August 2016) - Huber, Marcel; Huemer, Markus; Hofmann, Angela; Dumfort, Sabrina
Abstract: Over the last years, numerous gasification concepts have been developed to a reliable and commercially available state leading to a strongly increasing numbers of built plants. One of these describes a novel way in the thermochemical gasification of biomass by using a unique reactor design and operational mode – the floating-fixed-bed reactor. Comparable gasification concepts show bottlenecks in downsizing possibilities and tar concentration in product gas from fluidized bed gasification as well as problems of channeling or compaction of the fuel bed in fixed-bed systems. The idea of the floating-fixed-bed reactor is to build up a stable bulk bed, which is floating on the inlet gas stream from pyrolysis and oxidation. Without uncontrolled particle movement in the reduction reactor and only relative movement of the fuel particles within the bed, relatively long gas residence could be provided, resulting in low tar concentrations in the product gas. The technology has proven the potential to bypass issues of comparable gasification technologies and verified the advantages of the innovative reactor design in several long-term test runs on pilot plants and also commercial plants. Beside continuous improvement of the gasification technology, the current development aims for upscale possibilities and increased fuel flexibility.